2008
DOI: 10.1121/1.2967472
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual development of phoneme contrasts: How sensitivity changes along acoustic dimensions that contrast phoneme categories

Abstract: Listeners discriminate acoustic differences between phoneme categories at a higher level than similarly sized differences within phoneme categories. The question this paper aims to answer is how this pattern in perceptual sensitivity develops along an acoustic dimension that contrasts two non-native speech sounds: through acquired distinctiveness, through acquired similarity, or through a combination of the two. A pretest-training-post-test experiment was designed to study perceptual development directly, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 40 publications
8
24
1
Order By: Relevance
“…It may be that five sessions of training can only improve categorization of synthetic stimuli to a certain degree (note that post-test /i+/-/w/ categorization consistency was about the same as pre-/post-test /ae/-// consistency, a finding that confirmed the prediction that the latter contrast would suffer less from L1 spectral interference than the former). Even though training improved vowel identification, it did not lead to trainees being able to better discriminate the same contrast; these results are in line with those of Heeren and Schouten (2008) who successfully trained native Dutch speakers in identifying the Finish /t/-/t+/ contrast but found that trainees did not improve in their discrimination of the same contrast. The present work differs from Heeren and Schouten (2008) in terms of both the type of L2 contrasts tested (vowels vs consonants) and of the type of discrimination task used (adaptive vs nonadaptive), and so the replication of the lack of effect of identification-based auditory training on discrimination ability is noteworthy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It may be that five sessions of training can only improve categorization of synthetic stimuli to a certain degree (note that post-test /i+/-/w/ categorization consistency was about the same as pre-/post-test /ae/-// consistency, a finding that confirmed the prediction that the latter contrast would suffer less from L1 spectral interference than the former). Even though training improved vowel identification, it did not lead to trainees being able to better discriminate the same contrast; these results are in line with those of Heeren and Schouten (2008) who successfully trained native Dutch speakers in identifying the Finish /t/-/t+/ contrast but found that trainees did not improve in their discrimination of the same contrast. The present work differs from Heeren and Schouten (2008) in terms of both the type of L2 contrasts tested (vowels vs consonants) and of the type of discrimination task used (adaptive vs nonadaptive), and so the replication of the lack of effect of identification-based auditory training on discrimination ability is noteworthy.…”
Section: Discussionsupporting
confidence: 90%
“…Even though training improved vowel identification, it did not lead to trainees being able to better discriminate the same contrast; these results are in line with those of Heeren and Schouten (2008) who successfully trained native Dutch speakers in identifying the Finish /t/-/t+/ contrast but found that trainees did not improve in their discrimination of the same contrast. The present work differs from Heeren and Schouten (2008) in terms of both the type of L2 contrasts tested (vowels vs consonants) and of the type of discrimination task used (adaptive vs nonadaptive), and so the replication of the lack of effect of identification-based auditory training on discrimination ability is noteworthy. Further, Iverson and Evans (2009) found that despite improving in English identification accuracy, Spanish and German speakers did not improve in their English vowel space mapping after perceptual training, i.e., their best exemplar locations for English vowels were not closer to the target vowels post-training.…”
Section: Discussionsupporting
confidence: 90%
“…Hogen and Flege (2006) found that most early second-language (L2) learners were able to discriminate difficult English language vowel contrasts at near native listener levels, compared with near-chance level performance by Spanish monolingual listeners. Heeren and Schouten (2008) studied the effects of short- and long-term training on L2 learning when native speakers of Dutch listened to Finnish phoneme contrasts under a pretest-training-post-test design. They found that short-term training with non-native phoneme contrasts produces minimal changes in perceptual sensitivity, while with long-term training, advanced language learners can display perceptual sensitivity comparable to that in native listeners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, L2 learners tend to over-rely on length when distinguishing between non-native vowels for which length is only a secondary cue (such as the English tense-lax distinction), even when their L1 does not use length contrastively (e.g., native speakers of Spanish or Mandarin; Bohn, 1995; Escudero & Boersma, 2004). At the same time, however, the accessibility of length depends on the exact contrast (Wang, 2006), and L1 background does affect perception and learning of contrasts based on length (Hayes, 2002; McAllister et al, 2002; Goudbeek, Cutler, & Smits, 2008; Hayes-Harb & Masuda, 2008; Heeren & Schouten, 2008; Escudero et al, 2009; Pajak, 2013). In fact, differential perception of length contrasts can already be observed in 18-month-old infants learning a language with phonemic vs. non-phonemic length, such as Dutch (Dietrich, Swingley, & Werker, 2007) or Japanese (Mugitani, Pons, Fais, Werker, & Amano, 2009).…”
Section: Introductionmentioning
confidence: 99%